HIV disease and diabetes interact to affect brain white matter hyperintensities and cognition. (24th August 2018) - Wu, Minjie; Fatukasi, Omalara; Yang, Shaolin; Alger, Jeffery; Barker, Peter B.; Hetherington, Hoby; Kim, Tae; Levine, Andrew; Martin, Eileen; Munro, Cynthia A.; Parrish, Todd; Ragin, Ann; et al.
Abstract : Background: Since the onset of combination antiretroviral therapy use, the incidence of HIV-associated dementia and of HIV encephalitis has fallen dramatically. The present study investigates the extent of white matter hyperintensities (WMHs) among individuals with HIV disease, and factors that predict their presence and their impact on psychomotor speed. Methods: A total of 322 men participating in the Multicenter AIDS Cohort Study (185 HIV-infected, age: 57.5 ± 6.0) underwent MRI scans of the brain. T1 -weighted magnetization-prepared rapid gradient-echo (MP-RAGE) and T2 -weighted Fluid Attenuated Inversion Recovery (FLAIR) images were obtained and processed using an automated method for identifying and measuring WMHs. WMH burden was expressed as the log10 transformed percentage of total white matter. Results: There were no significant associations between WMHs and HIV disease. However, the extent of WMHs was predicted by age more than 60 (β = 0.17), non-white race (β = 0.14), glomerular filtration rate (β = −0.11), and the presence of diabetes (β = 0.12). There were no interactions between HIV status and age (β = −0.03) or between age and diabetes (β = 0.07). However, the interaction between HIV infection and diabetes was significant (β = 0.26). The extent of WMHs was significantly associated with performance on measures of psychomotor speed (β = 0.15). Conclusion: In today's therapeutic environment, in HIV-infected and HIV seronegative individuals, those factors which affect the cerebrovasculature are the best predictors of WMHs. Diabetes has a specific impact among HIV-infected, but not uninfected, men, suggesting the need for more aggressive treatment even in the prediabetes state, especially as WMHs affect cognitive functions.